1992
DOI: 10.1099/0022-1317-73-4-763
|View full text |Cite
|
Sign up to set email alerts
|

Electrotransfection of protoplasts from tomato, wild tomato, barley and chrysanthemum with tobacco mosaic virus RNA

Abstract: Protoplasts isolated from tomato, wild tomato, barley and chrysanthemum were electrotransfected with tobacco mosaic virus (TMV) RNA under almost the same optimum electric conditions: five square DC pulses of 50 ~ts duration at 500 to 800 V/cm, with the protoplasts suspended at 2 x 105/ml in 0-5 M-mannitol containing 100 ktM-MgC12 and 10 to 20txg/ml TMV RNA. ELISAs of these transfected protoplasts showed that the yields and the growth curves of the virus were quite similar, indicating a lack of host specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…In general, electrotransfection of the same amount of viral RNA into rapeseed protoplasts gave rise to Northern blot signals approximately 1.5-to twofold the intensity of those obtained using Chinese cabbage protoplasts. It has already been observed that the efficiency with which a virus replicates in a plant does not necessarily correlate with the efficiency at the protoplast level (discussed in Matsunaga et al, 1992). Indeed, Chinese cabbage rather than rapeseed plants are more commonly used as propagating hosts for TYMV, although it remains to be determined whether this could be correlated with higher efficiency of viral replication in host cells.…”
Section: Resultsmentioning
confidence: 99%
“…In general, electrotransfection of the same amount of viral RNA into rapeseed protoplasts gave rise to Northern blot signals approximately 1.5-to twofold the intensity of those obtained using Chinese cabbage protoplasts. It has already been observed that the efficiency with which a virus replicates in a plant does not necessarily correlate with the efficiency at the protoplast level (discussed in Matsunaga et al, 1992). Indeed, Chinese cabbage rather than rapeseed plants are more commonly used as propagating hosts for TYMV, although it remains to be determined whether this could be correlated with higher efficiency of viral replication in host cells.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments assessing replication of HaSV in protoplasts were done similarly except as noted. Pulse-label experiments were conducted by transferring the protoplasts after electroporation with 1.5 g of HaSV (5 ϫ 10 10 virions), 1.5 g of HaSV RNA, 1.5 g of TMV, and 0.16 g of TMV RNA (Matsunaga et al, 1992) in a six-well tray with medium containing 150 Ci of [ 32 P]orthophosphate (Amersham). After 3 days growth, the protoplasts were collected by roughly pipetting them from the tray, pelleted, and freeze-thawed to lyse them.…”
Section: Preparation and Electroporation Of Protoplastsmentioning
confidence: 99%